Avaliação da alteração dimensional de modelos obtidos a partir de moldagens com alginato tradicional e outro com desinfetante - Lemos, Ivana da Silva; Porto, Rosângela Oliveira; Alves, Bruno Pereira; Jassé, Fernanda Ferreira [UNESP]; Galvão, Marília Regalado [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Saad, José Roberto Cury [UNESP] (My University, 2010)
The present study aims at evaluating dimensional alteration of stone casts made from impressions with a standard irreversible hydrocolloid and an antimicrobial one. For this, an alginate without disinfectant (Type II Jeltrate) and other containing chlorhexidine (Type II Avagel) were used, which rose by the same regime of treatment: without disinfection; immersion; and spraying. A 1% sodium hypochlorite solution was used for 10 minutes. To obtain the impressions, a perforated impression tray was made from a standard metal model. After molding, the molds were washed in running water for 30 seconds to simulate removal of saliva. Then, with the exception of the control group, these molds were subjected to disinfection treatment. After 10 minutes they were washed again. 60 samples poured with type V special gypsum (Durone) were obtained, that were measured 3 times in a stereomicroscope (SZX12, Olympus) to record the average of dimensional alterations. The disinfection treatment did not bring significant changes in the models obtained from both alginate tested (standard p = 0.7102; with chlorhexidine p = 0.5832). The results showed a statistically significant and additional advantage of the traditional alginate on alginate with chlorhexidine, with respect to dimensional alteration (p < 0.05).

A proposta deste estudo foi avaliar a alteração dimensional de modelos de gesso obtidos a partir de moldes de alginato tradicional e alginatos suplementados com antimicrobiano. Foram utilizados um alginato sem desinfetante (Jeltrate tipo II) e outro suplementado com clorexidina (Avagel tipo II), que passaram pelos mesmos regimes de tratamento: sem desinfecção, imersão e spray. A solução usada foi o hipoclorito de sódio a 1% por 10 minutos. Foi utilizada para obtenção dos moldes uma moldeira perfurada confeccionada a partir de um modelo metálico padrão. Após a moldagem, os moldes foram lavados em água corrente por trinta segundos para simular remoção de saliva. Em seguida, com exceção do grupo controle, os moldes foram submetidos ao tratamento de desinfecção. Após 10 minutos, foram novamente lavados. Obtiveram-se sessenta corpos-de-prova vazados com gesso especial tipo V (Durone), que foram medidos três vezes em um Estereomicroscópio (SZX12, Olympus) para registro da média de alteração dimensional. O tratamento de desinfecção não provocou alteração significativa nos modelos obtidos de ambos os alginatos testados (tradicional p = 0,7102; com clorexidina p = 0,5832). Os resultados exibiram uma vantagem adicional e estatisticamente significante do alginato tradicional em relação ao alginato com clorexidina, no que diz respeito à alteração dimensional (p < 0,05).
Evaluation of the dimensional alteration of casts obtained from impressions with a traditional irreversible hydrocolloid and an antimicrobial one
Keywords: Dental impression materials; Chlorhexidine; Disinfection; Materiais para moldagem odontológica; Clorexidina; Desinfecção